2015
DOI: 10.4054/demres.2015.33.32
|View full text |Cite
|
Sign up to set email alerts
|

Residential mobility in early childhood

Abstract: BACKGROUNDUnderstanding residential mobility in early childhood is important for contextualizing influences on child health and well-being. OBJECTIVEThis study describes individual, household, and neighborhood characteristics associated with residential mobility for children aged 0−5. METHODSWe examined longitudinal data from the Early Childhood Longitudinal Study-Birth Cohort (ECLS-B), a nationally representative sample of children born in 2001. Frequencies described the prevalence of characteristics for four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Others have found that incomplete records were less likely to match and were often related to social disadvantage [43,44]. Frequent residential mobility, which is common in early childhood [45,46], is associated with increased risk of poor physical and/or mental health and such children are overrepresented in low income families, children with no fully employed adult in the household, and children in single-parent households [45][46][47]. Residential mobility, including a short period of time in class (< one month) before the EDI completion, may have contributed to unlinked records and vulnerability findings based on our inability to match on postal code in the RPDB and EDI where updates to each database may not occur simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that incomplete records were less likely to match and were often related to social disadvantage [43,44]. Frequent residential mobility, which is common in early childhood [45,46], is associated with increased risk of poor physical and/or mental health and such children are overrepresented in low income families, children with no fully employed adult in the household, and children in single-parent households [45][46][47]. Residential mobility, including a short period of time in class (< one month) before the EDI completion, may have contributed to unlinked records and vulnerability findings based on our inability to match on postal code in the RPDB and EDI where updates to each database may not occur simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies by Thomas, Stillwell, and Gould (2015) and Lawrence, Root, and Mollborn (2015) have examined the characteristics of mobile groups without life event data. These studies are important for understanding new cohort or population samples and cement the importance of broad characteristics in understanding mobility patterns.…”
Section: Theoretical Limitations Within the Literaturementioning
confidence: 99%
“…Our focus on early childhood is motivated by the foundational role of this life period [55] and its hypothesized high sensitivity to area influences [21]. While young children's daily activities tend to take place within the neighborhood, early childhood is also a life phase characterized by high residential mobility [23,24,56]. A further contribution of this study is that it complements its examination of neighborhood socio-economic composition at one point in time with a consideration of neighborhood change to account for residential mobility.…”
Section: Discussionmentioning
confidence: 99%